Astronomical applications of astrometry : ten years of exploitation of the Hipparcos satellite data - Perryman, M. A. C. (Cambridge University Press, 2009)
The Hipparcos satellite, developed and launched by the European Space Agency (ESA) in 1989, was the first space mission dedicated to astrometry - the accurate measurement of positions, distances, and proper motions of stars. Amongst the key achievements of its measurements are refining the cosmic distance scale, characterising the large-scale kinematic motions in the Solar neighbourhood, providing precise luminosities for stellar modelling, and confirming Einstein's prediction of the effect of gravity on starlight. This authoritative account of the Hipparcos contributions over the following decade is an outstanding reference for astronomers, astrophysicists and cosmologists. It reviews the applications of the data in different areas, describing the subject and the state-of-the-art before Hipparcos, and summarising all major contributions to the topic made by Hipparcos. It contains a detailed overview of the Hipparcos and Tycho Catalogues, their annexes and their updates. Each chapter ends with comprehensive references to relevant literature.